Genomic Epidemiology of Carbapenem- and Colistin-Resistant Klebsiella pneumoniae Isolates From Serbia: Predominance of ST101 Strains Carrying a Novel OXA-48 Plasmid - Palmieri, Mattia; D’Andrea, Marco Maria; Pelegrin, Andreu Coello; Mirande, Caroline; Brkic, Snezana; Cirkovic, Ivana; Goossens, Herman; Rossolini, Gian Maria; van Belkum, Alex (Frontiers in Microbiology, 2020)
Klebsiella pneumoniae is a major cause of severe healthcare-associated infections and often shows MDR phenotypes. Carbapenem resistance is frequent, and colistin represents a key molecule to treat infections caused by such isolates. Here we evaluated the antimicrobial resistance mechanisms and the genomic epidemiology of clinical K. pneumoniae isolates from Serbia. Consecutive non-replicate K. pneumoniae clinical isolates (n=2,298) were collected from seven hospitals located in five Serbian cities and tested for carbapenem resistance by disk diffusion. Isolates resistant to at least one carbapenem (n=426) were further tested for colistin resistance with Etest or Vitek2. Broth microdilution (BMD) was performed to confirm the colistin resistance phenotype, and colistin-resistant isolates (N=45, 10.6%) were characterized by Vitek2 and whole genome sequencing. Three different clonal groups (CGs) were observed: CG101 (ST101, N=38), CG258 (ST437, N=4; ST340, N=1; ST258, N=1) and CG17 (ST336, N=1). mcr genes, encoding for acquired colistin resistance, were not observed, while all the genomes presented mutations previously associated with colistin resistance. In particular, all strains had a mutated MgrB, with MgrBC28S being the prevalent mutation and associated with ST101. Isolates belonging to ST101 harbored the carbapenemase OXA-48, which is generally encoded by an IncL/M plasmid that was no detected in our isolates. MinION sequencing was performed on a representative ST101 strain, and the obtained long reads were assembled together with the Illumina high quality reads to decipher the blaOXA-48 genetic background. The blaOXA-48 gene was located in a novel IncFIA-IncR hybrid plasmid, also containing the extended spectrum β-lactamase-encoding gene blaCTX-M-15 and several other antimicrobial resistance genes. Non-ST101 isolates presented different MgrB alterations (C28S, C28Y, K2*, K3*, Q30*, adenine deletion leading to frameshift and premature termination, IS5-mediated inactivation) and expressed different carbapenemases: OXA-48 (ST3437 and ST336), NDM-1 (ST437 and ST340) and KPC-2 (ST258). Our study reports the clonal expansion of the newly emerging ST101 clone in Serbia. This high-risk clone appears adept at acquiring resistance, and efforts should be made to contain the spread of such clone.